Collision monitoring in elite male rugby union using a new instrumented mouth-guard - Waldron, M.; Jones, C.; Melotti, L.; Brown, R.; Kilduff, L. P. (The Journal of Sport and Exercise Science, 2021)
An instrumented mouth-guard and data analytics platform (PROTECHT) was used to compare collision metrics derived from linear and rotational accelerations of elite rugby union players according to position (forwards and backs), match role (starters and non-starters), match halves (first-and second-half) and six contact types. Analyses were performed at the level of individual collisions and across whole-matches. Fifteen male players from one elite-level rugby union team wore instrumented mouth-guards during10 matches. Collision metrics were analysed using the PROTECHT system. At the level of individual contacts, linear (P = 0.034) and rotational accelerations (P = 0.049) were larger in the second-half of matches. Rotational accelerations were highest for ball-carries (P < 0.05) compared to aerial challenges and rucks. Analysis of matches demonstrated no differences (P > 0.05) between backs and forwards, across all variables, while non-starters had higher mean rotational intensity (P = 0.006) and moderate-intensity collisions/min (P = 0.011; d = 0.69) comparedto starters. Linear load/min (P = 0.041) and moderate collision counts/min (P = 0.031) were also higher in the second-half when comparing all match performances but there were no differences (P > 0.05) among those playing both halves. The intensity of collisions increased in the second-half of matches and is likely explained by replacement players. This information can be used to support the utilisation of replacement players. The lower magnitude of head accelerations compared to previous studies requires further research to establish the accuracy of head impact thresholds in rugby union.